Beta-hydroxy-beta-methylglutaryl coenzyme a hydrolase of rat liver - Sipat, Abdullah; Sabine, John R. (Elsevier, 1981)
Beta-Hydroxy-beta-methylglutaryl coenzyme A hydrolase, or deacylase, (EC 3.1.2.5) is important, at least potentially, in the regulation of mammalian cholesterol synthesis. This is so for two reasons, both related to the enzyme generally regarded as rate-limiting for cholesterogenesis, namely beta-hydroxy-beta-methylglutaryl CoA reductase: (i) the hydrolase competes for the same substrate as the reductase and (ii) its end product, hydroxymethylglutamic acid, is a known inhibitor of the reductase. Consequently we have examined some of the properties of the hydrolase, as found in rat liver, after first developing a simple isotopic technique for its assay. Beta-Hydroxy-beta-methylglutaryl CoA hydrolase is both soluble and microsomal. The microsomal enzyme is inactivated by pre-incubation at 37 degree C, but not a 4 degree C, has an apparent pH optimum of approximately 7.6, and has Km and V values of 270 (microM) and 33.3 (nmol HMG/10 per mg protein), respectively, at 37 degree C. For the cytosolic enzyme the corresponding Km and V values are 830 and 111.1. From our observations it seems unlikely that beta-hydroxy-beta-methylglutaryl CoA hydrolase plays a significant role in the regulation of hepatic cholesterol synthesis since, in contrast to microsomal beta-hydroxy-beta-methylglutaryl coenzyme A reductase, we could find for the microsomal hydrolase no evidence of a diurnal rhythm of activity, no inhibition of activity by short-term cholesterol feeding and no evidence from Arrhenius-plot data for any membrane-mediated control of enzyme activity. Thus, the significance of the enzyme in mammalian systems remains unknown.